Regulatory Challenges and Solutions for Fintech in Turkey - Degerli, Kazim (Procedia computer science, 2019)
Regulators often have three different approaches when it comes to regulating FinTech; Ignore, liken, or regulate. As one of the most regulated sectors in Turkish economy, financial services are far from being ignored. FinTech companies in Turkey have been developing innovative products and services that provide great value for consumers and businesses. Fast pace of development in areas based on electronic services such as e-invoice, e-payments, e-government services, importance of FinTechs have become more apparent with their agility in taking action and offering innovative services. However, as agile as they might be, FinTech companies tend to ignore the regulations which financial institutions are subject to. “If it works here, it works everywhere” approach may have a serious downside when it comes to execution stage. From definition of the service to areas of application, to formation of the company and background of the investors, the ever-dictating financial sector regulations change dramatically from one country to another. As in the example of popular payment provider PayPal, failing to keep primary systems domestically may lead to a rejection of license application from BRSA (Banking Regulation and Supervision Agency) [1] Another example of such regulations is the need to do Due Diligence and monitor suspicious customer activity for AML/CTF purposes for some FinTechs in payment industry. Such requirements can be daunting for a technology-oriented point of view, and many of these companies face these facts at a later stage when they try to coexist or collaborate with other financial institutions. As these requirements may alter operational costs, human resources, and even IT infrastructure, they struggle to find investment or sign contracts with financial institutions. This study covers both successful and unsuccessful FinTech projects in payments and their position against regulations and offer remediations for better acceptance within Turkish financial sector.